C-REACTIVE PROTEIN IN DIABETIC PATIENTS BEFORE GASTRIC BYPASS AS A POSSIBLE MARKER FOR POSTOPERATIVE COMPLICATION - LINS,Daniel C. (2015)
Background : Obesity and type 2 diabetes mellitus are associated to inflammatory state, which can be set off by the adipose tissue, once it is a metabolically active organ that can cause a chronic mild inflammatory state. Aim : To evaluate the correlation between preoperative C-reactive protein and postoperative complications risk in obese patients (grades II and III) after Roux-en-Y gastric bypass, with and without type 2 diabetes mellitus. Methods : Between 2008 and 2013 were analysed 209 patients (107 with diabetes), presenting body mass index >40 kg/m2or >35 kg/m2with comorbidities. During the postoperative period, two groups were evaluated: with and without complications. Preoperative ultra-sensitive C-reactive protein was measured by immunonephelometry method. Results : Complications occurred in seven patients (pulmonary thromboembolism, fistula, two cases of suture leak, pancreatitis, evisceration and upper digestive hemorrhage). No statistical significance was found regarding lipid profile and C-reactive protein between patients with and without type 2 diabetes mellitus. When compared to each other, both groups (with and without complications) presented with statistical significance regarding C-reactive protein level (7,2 mg/dl vs 3,7 mg/dl, p=0,016) and had similar weight loss percentage after 3, 6 and 12 months follow-up. Conclusions : Preoperative C-reactive protein serum level was higher in the group which presented complications after Roux-en-Y gastric bypass when compared to the group without postoperative complications.